The effects of vitamin D supplementation on inflammatory biomarkers in patients with asthma: a systematic review and meta-analysis of randomized controlled trials - El Abd, Asmae; Dasari, Harika; Dodin, Philippe; Trottier, Helen; Ducharme, Francine M. (Frontiers in Immunology, 2024)
Background: While the association between vitamin D and several inflammatory biomarkers in asthma patients has been extensively reported, it remains unclear whether supplementation modifies these biomarkers. This review aims to evaluate the impact of vitamin D supplementation on inflammatory biomarkers measured in vivo in individuals with asthma.We conducted a systematic review of randomized controlled trials (RCTs) published until November 2022 in six electronic databases evaluating the impact of vitamin D supplementation (any dose, form, administration route, frequency, or duration) compared to placebo in children or adults. The two co-primary outcomes were serum IgE and blood eosinophils reported at the endpoint. Secondary outcomes included other markers of type 2 inflammation (e.g., sputum eosinophils, fractional exhaled nitric oxide, etc.), anti-inflammatory biomarkers (e.g., interleukin (IL)-10, etc.), markers of non-type 2 inflammation (e.g., high-sensitivity C-reactive protein, etc.), and non-specific biomarkers (e.g., macrophages, etc.). Data were aggregated using fixed or random effect models.Results: Thirteen RCTs (5 in adults, 5 in pediatric patients, and 3 in mixed age groups) testing doses of vitamin D supplementation ranging from 800 to 400,000 IU over periods of 6 weeks to 12 months were included. Eight studies provided data on serum IgE and four on blood eosinophils. As secondary outcomes, three studies reported on sputum eosinophils, four on FeNO, five on serum IL-10, and two on airway IL-10. Compared to placebo, vitamin D supplementation had no significant effect on serum IgE (Mean difference [MD] [95% CI]: 0.06 [-0.13, 0.26] IU/mL), blood eosinophils (MD [95%